(untitled) (CIPEEX, 2022)
THIS TEXT IS AN EXPERIENCE REPORT OF ACTIVITIES DEVELOPED IN THE FAMILY AND COMMUNITY MEDICINE MODULE III IN THE 3RD PERIOD OF THE MEDICAL COURSE. THE ACTIVITY WAS CARRIED OUT AT THE LIONS ANHANGUERA SCHOOL IN THE CITY OF ANÁPOLIS - GO, WITH MONITORING BY THE PRECEPTORS OF THE BASIC FAMILY HEALTH UNIT - VILA FORMOSA. THE THEMES WORKED ON IN THE ACTIVITIES WERE BULLYING, MENTAL HEALTH AND THE SOCIAL INCLUSION OF INDIVIDUALS WITH PHYSICAL AND INTELLECTUAL DISABILITIES. BULLYING AND CYBERBULLYING CAN HAVE A SIGNIFICANT IMPACT ON MENTAL HEALTH, QUALITY OF LIFE AND RISK BEHAVIOURS, AND ITS CONSEQUENCES CAN MANIFEST IN FUTURE PROSPECTS AND EMPLOYABILITY. THUS, THE PROJECT AIMED TO PROVIDE CHILDREN AND TEACHERS OF THE RESPECTIVE CLASSES WITH AN AWARENESS OF MUTUAL RESPECT, EQUALITY, EQUITY AND SOCIAL INCLUSION.